INTEGRATION OF LOCAL ETHNOMATHEMATICS BASED ON ARTIFICIAL INTELLIGENCE (AI) IN ENHANCING STUDENTS’ CRITICAL THINKING SKILLS - Herwandi Sape; Andi Mulawakkan Firdaus; Arwin Wahyu Saputra; Muh. Fachrullah Amal (Jurnal Penalaran dan Riset Matematika, 2025)
This study aims to examine the effect of integrating local ethnomathematics based on Artificial Intelligence (AI) on students’ mathematical critical thinking skills. The research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The study was conducted at SMA Negeri 3 Maros, involving 54 eleventh-grade students divided into an experimental class (27 students) and a control class (27 students). The experimental class received mathematics instruction through the integration of local ethnomathematics supported by an AI-based adaptive learning system, while the control class was taught using conventional methods. Data were collected using a critical thinking test administered as pretest and posttest, based on indicators of analysis, evaluation, inference, and conclusion. The results revealed that the experimental class achieved a higher mean posttest score (88.40) compared to the control class (83.20). The N-Gain score of the experimental class (0.78; very high category) was also greater than that of the control class (0.68; high category). Independent samples t-test indicated a significant difference between the two groups (p < 0.05). These findings demonstrate that integrating local ethnomathematics with AI significantly enhances students’ mathematical critical thinking skills and provides an innovative, contextual, and adaptive learning alternative.